Immunization with individual proteins of the Lrp/AsnC family induces protection against Brucella melitensis 16M challenges in mice - Wang, Xinhui; An, Chang; Yang, Mingjuan; Li, Xinran; Ke, Yuehua; Lei, Shuangshuang; Xu, Xiaoyang; Yu, Jiuxuan; Ren, Hang; Du, Xinying; Wang, Zhoujia; Qiu, Yefeng; et al. (Frontiers in Microbiology, 2015)
Brucellosis is one of the most common zoonoses worldwide. Subunit vaccines are promising for the prevention of human brucellosis. In our previous protective antigen screening studies, we identified a new protective antigen, BMEI0357, which belongs to the Lrp/asnC protein family, a conserved transcriptional regulator in bacteria that is absent in eukaryotes. In the present study, the Brucella genome annotation was screened and a total of 6 proteins were identified as members of the Lrp/AsnC family. Lrp/AsnC proteins have 2 domains that are conserved among the family members. However, sequence similarities between these proteins ranged from 9% to 50%, indicating high sequence heterogeneity. To test whether proteins of this family have similar characteristics, all 6 proteins were cloned and expressed in Escherichia coli. The recombinant proteins were purified and their protective efficacy was evaluated in BALB/c mice challenged with Brucella melitensis 16M. The results show that all 6 Lrp/AsnC proteins could induce a protective immune response against Brucella melitensis 16M. Antibodies against the Lrp/AsnC proteins were detected in the immunized mice. However, levels of antibodies against these proteins were relatively variable in human brucellosis sera. Taken together, our results show that these 6 proteins of the Lrp/AsnC family in Brucella could induce protective immune responses in mice.